Ultradeformable archaeosomes for needle free nanovaccination with Leishmania braziliensis antigens - Higa, Leticia H. (2016)
Total antigens from Leishmania braziliensis promastigotes, solubilized with sodium cholate (dsLp), were formulated within ultradeformable nanovesicles (dsLp-ultradeformable archaeosomes, (dsLp-UDA), and dsLp-ultradeformable liposomes (dsLp-UDL)) and topically administered to Balb/c mice. Ultradeformable nanovesicles can penetrate the intact stratum corneum up to the viable epidermis, with no aid of classical permeation enhancers that can damage the barrier function of the skin. Briefly, 100 nm unilamellar dsLp-UDA (soybean phosphatidylcholine: Halorubrum tebenquichense total polar lipids (TPL): sodium cholate, 3:3:1 w:w) of -31.45 mV Z potential, containing 4.84 ± 0.53% w/w protein/lipid dsLp, 235 KPa Young modulus were prepared. In vitro, dsLp-UDA was extensively taken up by J774A1 and bone marrow derive cells, and the only that induced an immediate secretion of IL-6, IL-12p40 and TNF-α, followed by IL-1β, by J774A1 cells. Such extensive uptake is a key feature of UDA ascribed to the highly negatively charged archaeolipids of the TPL, which are recognized by a receptor specialized in uptake and not involved in downstream signaling. Despite dsLp alone was also immunostimulatory on J774A1 cells, applied twice a week on consecutive days along 7 weeks on Balb/c mice, it raised no measurable response unless associated to UDL or UDA. The highest systemic response, IgGa2 mediated, 1 log lower than im dsLp Al2O3, was elicited by dsLp-UDA. Such findings suggest that in vivo, UDL and UDA acted as penetration enhancers for dsLp, but only dsLp-UDA, owed to its pronounced uptake by APC, succeeded as topical adjuvants. The actual TPL composition, fully made of sn2,3 ether linked saturated archaeolipids, gives the UDA bilayer resistance against chemical, physical and enzymatic attacks that destroy ordinary phospholipids bilayers. Together, these properties make UDA a promising platform for topical drug targeted delivery and vaccination, that may be of help for countries with a deficient healthcare system.